Nano-curcumin improves glucose indices, lipids, inflammation, and Nesfatin in overweight and obese patients with non-alcoholic fatty liver disease (NAFLD): a double-blind randomized placebo-controlled clinical trial - Jazayeri-Tehrani, Seyed Ali; Rezayat, Seyed Mahdi; Mansouri, Siavash; Qorbani, Mostafa; Alavian, Seyed Moayed; Daneshi-Maskooni, Milad; Hosseinzadeh-Attar, Mohammad-Javad (Nutrition & Metabolism, 2019)
Since lifestyle changes are main therapies for non-alcoholic fatty liver disease (NAFLD), changing dietary components (nutritional or bioactive) may play a parallel important role. Few studies have assessed the effects of curcumin on NAFLD (mainly antioxidant and anti-inflammatory effects). We aimed to determine the effects of nano-curcumin (NC) on overweight/obese NAFLD patients by assessing glucose, lipids, inflammation, insulin resistance, and liver function indices, especially through nesfatin.